Social support, self-efficacy, self-esteem, and self-management behaviors among people living with HIV/AIDS in China: a structural equation modeling analysis - Haitao Huang; Ling Tu; Xiaona Zhang; Liao Zhang; Jianxiong Zhang; Qin Liu; Qianwen Liu; Ying Liu; Hong Chen (BMC Public Health)
Abstract Background Understanding the psychosocial factors influencing self-management behaviors among people living with HIV/AIDS (PLWHA) is crucial for effective medical interventions and improving their quality of life. However, few studies have explored the psychosocial mechanisms influencing self-management behaviors among PLWHA in China. This study, conducted in accordance with STROBE guidelines, uses SEM to explore the roles of social support, self-efficacy, and self-esteem in predicting self-management behaviors among Chinese PLWHA. Methods From March 2023 to July 2023, a convenience sample of 282 PLWHA, recruited from one designated AIDS hospital and one Centers for Disease Control and Prevention in Sichuan Province, China, was surveyed. Data were collected via four validated self-report scales (the Social Support Rating Scale, the General Self-Efficacy Scale, the Self-Esteem Scale, and the HIV/AIDS Patient Self-Management Scale). Structural equation modeling was used to assess the relationships among social support, self-efficacy, self-esteem, and self-management behaviors. Results The new model demonstrated acceptable fit parameters (χ 2 /df = 2.15, GFI = 0.96, AGFI = 0.93, CFI = 0.93, IFI = 0.94, RMSEA = 0.05). The direct effect of social support on self-management behaviors was significant (β = 0.117, P < 0.05). In addition, self-efficacy and self-esteem played significant mediating roles in the influence of social support on self-management behaviors, accounting for 38.73% and 22.79% of the total effect, respectively. Moreover, they served as chain mediators, contributing 9.80% to the total effect. Conclusions These findings contribute to our understanding of the psychosocial dynamics influencing self-management behavior in Chinese PLWHA and have broader implications for populations in other countries. Targeted interventions that enhance social support, self-efficacy, and self-esteem could be applied in various cultural contexts to improve self-management practices among PLWHA globally.